(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
Through linguistics, we analyze how language encodes concepts. This is done with the help of meaning explication and frame analysis as well as contextual analysis and conceptual metaphor analysis. Universal aspects of the concept of "ugliness" and cultural influences in different languages, allomorphism emerge as a result of comparison of prototype symbols and valuable concepts that embody national-cultural values. In this article, the words in the lexical-semantic field of ugliness-ugly were compared through examples used in a historical book ‘A new ride to Khiva’ by R. Jefferson. Our analysis shows that the basic phenomena of intuition, assessment, and feeling are important for the understanding of ugliness, which prepares the ground for the increase of human experience and knowledge and the creation of the concept.